2021
DOI: 10.1007/s13346-020-00888-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating hesperetin nanocrystals with tailor-made sizes for the prevention and treatment of Alzheimer’s disease

Abstract: Poor aqueous solubility of drug substances is associated with poor bioavailability and thus hampers the effective use of many potent active pharmaceutical ingredients. Various strategies to overcome poor solubility are available, whereby drug nanocrystals represent one of the most powerful formulation strategies to enhance the kinetic solubility and dissolution rate of poorly soluble drugs. Nanocrystals are simply obtained by milling large-sized drug powders to sizes < 1 µm. The so obtained nanocrystals pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…A possible explanation could be the particle size of the nanocrystals. In a previous study, we determined that Hst with smaller particles had a greater effect on elevating ATP levels in SH-SY5Y-APP wt cells compared to larger ones [25]. Similar, most studies have shown that the particle size has an impact on cell functions [48][49][50].…”
Section: Effect Of Hesperetin On Mitochondrial Function In Sh-sy5y-mock and -App 695 Cellsmentioning
confidence: 53%
See 3 more Smart Citations
“…A possible explanation could be the particle size of the nanocrystals. In a previous study, we determined that Hst with smaller particles had a greater effect on elevating ATP levels in SH-SY5Y-APP wt cells compared to larger ones [25]. Similar, most studies have shown that the particle size has an impact on cell functions [48][49][50].…”
Section: Effect Of Hesperetin On Mitochondrial Function In Sh-sy5y-mock and -App 695 Cellsmentioning
confidence: 53%
“…All vials were stirred on a magnetic stirring plate (IKA RCT standard, Haan, Germany) at 1200 rpm in ice water for 8 h. After production and before treatment of cells, particle size was strictly monitored. The average particle size was determined by photon correlation spectroscopy using a ZetaSizer NanoZS (Malvern-Panalytical, Kassel, Germany), laser diffraction using a Mastersizer 3000 (Malvern-Panalytical, Kassel, Germany), and light microscopy using an Olympus BX53 light microscope (Olympus Cooperation, Tokyo, Japan) equipped with an Olympus SC50 CMOS color camera (Olympus Soft Imaging Solutions GmbH, Nord, Germany) according to [25]. Since polyphenols have the potential to act as pan-assay interference compounds [36], we used PAINS-Remover at https://www.…”
Section: Hesperetin Nanocrystalsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar double-targeted nanosystem loaded with RESV showed neuroprotective effects in an AD mouse model [232]. [236,237] NLCs: nanostructured lipid carriers, SLN: solid lipid nanoparticles, SPION: superparamagnetic iron oxide nanoparticles, SLN/RVG29/TPP: Solid lipid nanoparticles attached to rabies virus glycoprotein (RVG29) and triphenylphosphonium (TPP) moiety, GSH: glutathione, GSH-PX: glutathione peroxidase, SOD: superoxide dismutase, CAT: catalase, ETC: electron transport chain, Aβ: amyloid β protein, RES: reticuloendothelial system, PD: Parkinson disease, AD: Alzheimer's disease.…”
Section: Nanosystems Containing Antioxidative and Neuroprotective Plant Chemicals To Repair Mitochondrial Function In Neurodegenerationmentioning
confidence: 99%